BFEX: A Toolbox for Finite Element Analysis With Fossils and Blender - E. Miguel Díaz de León‐Muñoz; Romain Boman; Gabriel S. Ferreira (Ecology and Evolution)
ABSTRACT (1) Finite Element Analysis (FEA) has become a common method when studying fossils. As computer systems and tools advance, new software like Fossils is developed to make FE analyses more efficient. (2) However, the preparation of input data for analysis remains time‐consuming. In particular, surface mesh cleaning and the selection of groups of nodes for the boundary conditions (muscle forces and prescribed displacements) usually require graphical programs that are either not well adapted to this task or require an expensive license. (3) To address this, we introduce BFEX (Blender Finite Element eXporter), a Blender add‐on that simplifies model creation for FEA with Fossils. (4) This approach helps streamline the entire process, making it more user‐friendly.